(untitled) (Research, Society and Development, 2023)
Glaucoma is a highly prevalent neurodegenerative disease in Brazil, characterized by progressive deficits in the visual field, blindness being a serious consequence of its late diagnosis. This study aims to identify the epidemiological aspects of hospitalizations for glaucoma in Brazil, between the years 2012 and 2021. It is a descriptive epidemiological study, whose data were obtained through the Department of Informatics of the Unified Health System (DATASUS), in addition to scientific articles in the PUBMED, SCIELO and GOOGLE SCHOLAR databases, referring to the period from 2018 to 2023. The data obtained by DATASUS were reorganized into tables and analyzed later. It was seen that, in the last 10 years, hospitalizations for glaucoma in Brazil were higher in the Southeast region (45.72%), with the majority of consultations being elective (78.75%). In all years, the number of hospitalizations was more prevalent in men, with the greatest difference in total value between genders in 2020 (14%). Regarding age group, there was a predominance of hospitalizations in adults aged 60-69 years (29.32%). In addition, the white race had the highest number of hospitalizations (50.76%). Therefore, the high findings in the number of hospitalizations for glaucoma in Brazil demonstrate the need to intensify early diagnosis practices, as well as adequate therapeutic interventions, aimed at preserving ocular health.